Retrieving Molecular Structural Information and Tracking HNC/HCN Isomerization Process with High Harmonic Generation by Ultrashort Laser Pulses - Ty, Nguyen Ngoc; Hoang, Le Van; Tuoc, Vu Ngoc; Thu, Le Anh (Communications in Physics, 2012)
We investigate the possibility of applying the iterative method,suggested in our previous work, for HCN molecule and its HNCisomer. We found that the high-order harmonic generation (HHG)spectra are quite insensitive to the change of H-C (or H-N) bondlength so that only the inter-nuclear C-N distance can beretrieved from the high-order harmonic spectra using ultrashortintense lasers. Furthermore, by analyzing the HHG spectra emittedby HCN during the chemical reaction path of isomerization weidentify the intensity peaks nearby the stable, meta-stable andtransition states. This finding can be useful for tracking theHNC/HCN isomerization process